Putative Roles of SETBP1 Dosage on the SET Oncogene to Affect Brain Development - Antonyan, Lilit; Ernst, Carl (Frontiers in Neuroscience, 2022)
Mutations in SET BINDING PROTEIN 1 (SETBP1) cause two different clinically distinguishable diseases called Schinzel–Giedion syndrome (SGS) or SETBP1 deficiency syndrome (SDD). Both disorders are disorders of protein dosage, where SGS is caused by decreased rate of protein breakdown due to mutations in a proteosome targeting domain, and SDD is caused by heterozygous loss-of-function mutations leading to haploinsufficiency. While phenotypes of affected individuals support a role for SETBP1 in brain development, little is known about the mechanisms that might underlie this. The binding partner which gave SETBP1 its name is SET and there is extensive literature on this important oncogene in non-neural tissues. Here we describe different molecular complexes in which SET is involved as well as the role of these complexes in brain development. Based on this information, we postulate how SETBP1 protein dosage might influence these SET-containing molecular pathways and affect brain development. We examine the roles of SET and SETBP1 in acetylation inhibition, phosphatase activity, DNA repair, and cell cycle control. This work provides testable hypotheses for how altered SETBP1 protein dosage affects brain development.